Problematika Lembaga Mahkamah Agung Dalam Penegakan Hukum Di Indonesia - -, muntaha (Jurnal Hukum & Pembangunan, 2019)
A process of law enforcement was considerably as part of system of judicature as well as a part of procedure of justice. The issue on this research is “What is the problematic in Supreme Court related to law enforcement in Indonesia”. This study principally aimed: a. Academically, as further base data. b. Practically, as evaluated material for Supreme Court in adjusting related to law enforcement in institutional jurisdiction. The used method in this research is by means of conceptual approach. Subsequently, the outcome is that problematic of law enforcement toward Supreme Court are: a. Integrity of law enforcer that has relatively weak. b. Lack of judicial administration system. c. Relating to regulation.